PEMANFAATAN TEKNOLOGI DIGITAL YANG BELUM OPTIMAL PADA PROSES PEMBELAJARAN DI SMP NEGERI 30 SELUMA - Marghareta; Adi Asmara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to deeply analyze the level of digital technology utilization in the learning process at secondary educational institutions, specifically at SMP Negeri 30 Seluma, and comprehensively identify the multidimensional factors that contribute to its suboptimal use. The research method applied in this academic study is a qualitative approach with critical literature review and descriptive empirical analysis of contemporary learning practices in Indonesia. The results of the literature review and data analysis consistently indicate that although digital technology hardware and software are widely available in educational institutions, their implementation in the classroom remains very limited to fulfilling formal administrative functions and basic mechanical presentation instruments, and does not fully support the direction of integrative pedagogical transformation. The main determinants include low digital and pedagogical competencies of educators, limited quality and quantity of information technology infrastructure, a less adaptive leadership paradigm, and the persistence of the conventional teacher-centered learning paradigm. This study confirms that optimizing digital technology in schools requires an integrated framework that includes strengthening pedagogical competencies, digital literacy based on the TPACK model, restructuring the school's operational curriculum, and the formulation of adaptive and sustainable regional education policies.